Impact Export Diversification on Exchange Rate Regime Choice - Mayangsari, Eka Putri; Handoyo, Rosanto Dwi (Journal of Developing Economies, 2017)
The choice of exchange rate regime is the most relevant decision in the economic world that must be faced by the economic authority until now. Exchange rate regime that is applied by one country become a controversial debate after the Asia's crisis in the year 1997-1998, especially for developing countries and emerging economies in Asia. The purpose of this research is to see the impact of export diversification, intensive margin and extensive margin to the choice of the exchange rate regime in nine emerging and developing countries in Asia 1991-2014. This research uses the panel logistic regression model to analyze the two model that are used in the research; they are: model 1 (the impact of export diversification to the exchange rate regime),and model 2 (the impact of extensive margin and intensive margin to the exchange rate regime. To avoid and to lessen the chances of endogeneity problem therefore, all the independent variables and the control variable must be lagged in one period. The results of the regression show that export diversification have a significant positive impact on the exchange rate regime. When export diversification is decomposed into intensive margin and extensive margins, the result shows that the extensive margins also have a significant positive impact towards the exchange rate regime, while the intensive margin does not show any significant impact towards the exchange rate regime choice. Keywords: Exchange Rate Regime, Export Diversification, Intensive Margin, Extensive Margin, Emerging and Developing Countries in Asia.JEL: F31, L25, O53